Creep of Sn-0.3Ag-0.7Cu solder in electronic packaging: Experiment and simulation - Yuezong Zheng; Junchen Liu; Hongchao Ji; Xiaomin Huang; Wenchao Xiao; Abdullah Aziz Saad (Journal of Materials Research and Technology)
In contemporary society, the growing reliance on electronic devices has necessitated the phasing out of traditional Sn–Pb solder due to its health hazards, prompting a transition to environmentally friendly, lead-free alternatives.This study aims to address the challenges of poor interfacial reliability and high cost associated with eutectic Sn–Ag–Cu solders by investigating the creep properties and service life of a low-silver solder alloy, Sn-0.3Ag-0.7Cu, as a filler material.The creep behavior of Sn-0.3Ag-0.7Cu was analyzed through creep testing, and fracture modes were identified via microstructural and fracture surface analysis.The Anand viscoplastic model was employed to simulate and calibrate the creep behavior, with its accuracy validated via thermal cycling experiments.Furthermore, the creep behavior of Ball Grid Array (BGA) solder joints was simulated using Abaqus software to examine the impact of creep on joint longevity and the influence of temperature on performance.